Amateur telescope making in the internet age findings parts, getting help, and more - Clark, Robert L. (Patrick Moore's Practical Astronomy Series, 2011)
The Internet Age is changing everything about human invention and the use of technology. The change has been compared to that of the introduction of printing. Making your own telescope isn't what it used to be, either, thanks partly to the Internet. The old days of grinding and polishing are gone unless you want to do it! You can now assemble a great instrument from a wide range of affordable Internet-available components, new or used. The Internet is the new parts junkyard, with stuff from all over the world for you to pick through, day or night. In this book you will find out what's generally available and how to access it. You will learn how to evaluate optical components and combine them from diverse Internet sources. You will get many ideas on how to make the parts that you don't buy or scrounge and how to restore old lenses and mirrors. And you will learn some elementary physics of designing ergonomic comfortable telescopes. Navigating your way around the possibilities is easy using this valuable and timely resource. With Robert Clark's help you can get the best that the Internet has to offer. Get started now!